Design of an equipotential grounding system for pulsed power laboratory / Mohd Nadzri Abu Bakar - Abu Bakar, Mohd Nadzri (1997)
The objective of this project is to construct an equipotential ground in terms of grid system for the pulsed power laboratory of the school of Electrical Engineering, ITM, Shah Alam.